Tumor imaging using radiolabelled matrix metalloproteinase-activated anthrax proteins - Xavier, M; Liu, S; Bugge, T; Baguna-Torres, J; Mosley, M; Hopkins, S; Allen, P; Berridge, G; Vendrell, I; Fischer, R; Kersemans, V; Smart, S; et al. (Society of Nuclear Medicine and Molecular Imaging, 2019)
Purpose: Increased activity of matrix metalloproteinases (MMPs) is associated with worse prognosis in different cancer types. The protective antigen (PA-WT) of the binary anthrax lethal toxin was modified to form a pore in cell membranes only when cleaved by MMPs (PA-L1). Anthrax lethal factor (LF) is then able to translocate through these pores. Here, we used an 111In-radiolabelled form of LF with the PA/LF system for non-invasive in vivo imaging of MMP activity in tumour tissue by single photon emission computed tomography (SPECT). Methods: MMP-mediated activation of PA-L1 was correlated to anthrax receptor expression and MMP activity in a panel of cancer cells (HT1080, MDA-MB-231, B8484 and MCF7). Uptake of 111In-radiolabelled PA-L1, 111In-PA-WTK563C or 111In-LFE687A (a catalytically inactive LF mutant) in tumour and normal tissues was measured using SPECT/CT imaging in vivo. Results: Activation of PA-L1 in vitro correlated with anthrax receptor expression and MMP activity (HT1080>MDA-MB-231>B8484>MCF7). PA-L1-mediated delivery of 111In-LFE687A was demonstrated, and corroborated using confocal microscopy with fluorescently labelled LFE687A. Uptake was blocked by the broad-spectrum MMP inhibitor GM6001. In vivo imaging showed selective accumulation of 111In-PA-L1 in MDA-MB-231 tumour xenografts (5.7±0.9%ID/g) at 3 h post intravenous administration. 111In-LFE687A was selectively delivered to MMP-positive MDA-MB-231 tumour tissue by MMP-activatable PA-L1 (5.98±0.62%ID/g), but not by furin cleavable PA-WT (1.05±0.21%ID/g), or a non-cleavable PA variant control, PA-U7 (2.74 ± 0.24%ID/g). Conclusion: Taken together, our results indicate that radiolabelled forms of mutated anthrax lethal toxin hold promise for non-invasive imaging of MMP activity in tumour tissue.